Exploring Students’ Critical Thinking Skills Through an Analysis of Their Responses to Trigonometry Problems - Ramadhan, Dadan; Jatisunda, Mohamad Gilar (Papanda Publisher, 2025)
This study aims to analyze students’ critical thinking skills in solving trigonometry problems using a qualitative case study approach. The participants were 29 twelfth-grade students from SMAN 1 Kadipaten. Data were collected through classroom observations, students’ written responses, and semi-structured interviews and were analyzed using NVivo 14 software. The findings revealed that only a small proportion of students demonstrated adequate critical thinking indicators, particularly in the areas of interpretation, analysis, inference, and evaluation. While 69% of students were able to construct appropriate mathematical models, only 31% correctly applied relevant formulas, and merely 3% succeeded in accurately stating the final answers. The interview results supported the analysis, indicating that many students faced conceptual misunderstandings, procedural difficulties, and lacked reflective thinking in validating their solutions. These findings underscore the need to enhance students’ critical thinking skills through visual learning tools, reflective discussions, and contextual problem-solving exercises. This study contributes to the development of diagnostic assessment instruments and the design of adaptive instructional strategies in mathematics education, particularly for complex topics such as trigonometry.